Genetic co-administration of soluble PD-1 ectodomains modifies immune responses against influenza a virus induced by DNA vaccination - Tannig, Pierre; Peter, Antonia Sophia; Lapuente, Dennis; Klessing, Stephan; Schmidt, Anna; Damm, Dominik; Tenbusch, Matthias; Überla, Klaus; Temchura, Vladimir (Vaccines, 2020)
Due to the low efficacy and the need for seasonal adaptation of currently licensed influenza A vaccines, the importance of alternative vaccination strategies is increasingly recognized. Considering that DNA vaccines can be rapidly manufactured and readily adapted with novel antigen sequences, genetic vaccination is a promising immunization platform. However, the applicability of different genetic adjuvants to this approach still represents a complex challenge. Immune checkpoints are a class of molecules involved in adaptive immune responses and germinal center reactions. In this study, we immunized mice by intramuscular electroporation with a DNA-vaccine encoding hemagglutinin (HA) and nucleoprotein (NP) of the influenza A virus. The DNA-vaccine was applied either alone or in combination with genetic adjuvants encoding the soluble ectodomains of programmed cell death protein-1 (sPD-1) or its ligand (sPD-L1). Co-administration of genetic checkpoint adjuvants did not significantly alter immune responses against NP. In contrast, sPD-1 co-electroporation elevated HA-specific CD4+ T cell responses, decreased regulatory CD4+ T cell pools, and modulated the IgG2a-biased HA antibody pattern towards an isotype-balanced IgG response with a trend to higher influenza neutralization in vitro. Taken together, our data demonstrate that a genetic DNA-adjuvant encoding soluble ectodomains of sPD-1 was able to modulate immune responses induced by a co-administered influenza DNA vaccine.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Checkpoint blockade; DNA adjuvants; DNA vaccine; Immunomodulation; Influenza A; Intramuscular electroporation; Soluble PD-1; Soluble PD-L1